Epidemiological characteristics and influencing factors of hand, foot, and mouth disease outbreaks in Jiangsu province, 2010 - 2022: a register data analysis - Mingyang LI; Xiaoqing CHENG; Ye WEI; Huan FAN; Xuefeng ZHANG; Changjun BAO; Qingxiang SHANG; Hong JI (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze epidemiological characteristics and determinants of hand, foot, and mouth disease (HFMD) outbreaks in Jiangsu province over the period of 2010 to 2022 for developing local HFMD prevention and control measures. MethodsThe data on 238 HFMD outbreaks reported in Jiangsu province from 2010 through 2022 were collected from the Public Health Emergency Information Management System of the Chinese Center for Disease Control and Prevention. The epidemiological characteristics of the HFMD outbreaks were described using statistical analysis. The spatial distribution characteristics of the outbreaks were analyzed using ArcGIS10.7 and GeoDa1.18 software. The main influencing factors of the incidence and duration of the HFMD outbreaks were analyzed using a unconditional multivariate logistic regression model. ResultsA total of 238 outbreaks of HFMD were reported in the province during the study period, involving a total of 167 934 individuals exposed to the epidemic and resulting in 5 296 confirmed cases. The median attack rate for these outbreaks was 3.43%. The HFMD outbreaks were more frequently observed during the spring season (March to May) and autumn season (September to November), accounting for 36.97% and 29.83% of all outbreaks respectively. Furthermore, 68.07% of the outbreaks occurred in the southern region of the province. Almost all (99.16%) of these outbreaks took place in childcare institutions and schools. The time interval between incidence and identification ranged from 0 to 44 days (median = 8 days), while the outbreak duration varied from 3 to 78 days, with a median duration of 15.5 days. The predominant strains responsible for the HFMD outbreaks differed by year: Coxsackievirus A16 (Cox A16) was prevalent in 2010, 2012, 2014, 2015, 2018, 2019, and 2021; enterovirus 71 (EV71) dominated in 2011, 2013, and 2017; Coxsackievirus (Cox A6) was prominent in 2020; and both Cox A16 and EV71 were significant contributors in 2016; finally, Cox A16 and Cox A6 were identified as major strains in 2022. Geographically speaking, the HFMD outbreaks exhibited an aggregated distribution pattern with high-high clustering areas primarily located within three districts in Wuxi city, a district and a prefecture in Changzhou city, and three districts in Lianyungang city. Results obtained from multivariate logistic regression analysis indicated that certain characteristics were associated with higher attack rates among these outbreaks. These included being caused by Cox A16 or multiple viruses, having an epidemic duration lasting 21 days or longer, and being reported by schools, health centers, and education department. On the other hand, outbreaks occurring outside childcare institutions tended to have lower attack rates. Additionally, outbreaks classified as general epidemics, taking place in towns, and having a lag identification time of 15 days or more were more likely to have a longer epidemic duration. ConclusionThe HFMD outbreaks in Jiangsu province from 2010 to 2022 predominantly occurred during the spring and autumn seasons, with Cox A16 as the predominant strain. The southern region of Jiangsu province was the clustering area for the HFMD outbreaks. The main factors influencing the incidence and duration of these outbreaks include the outbreak setting, type of predominant virus, epidemic duration, reporting institution and epidemic level, location of the site, and lag time of epidemic identification.